(untitled) (Confluenţe Bibliologice, 2025)
This article evoked a festive meeting dedicated to Librarian Day in Moldova attended by Bălţi academic librarians . At the meeting were announced the results of ALRM National Contests „The Best Librarian of the Year 2015”, „The best works in the ﬁeld of library and information science in 2015”, The Republican Contest „The Library – a partner in promoting intellectual property” organized by AIP. The worthiest librarians were mentioned with diplomas and prizes.